The Effect of Blast-Hole Arrangement, Delay Time, and Decoupling Charge on Rock Damage and Vibration Attenuation in Multihole Blasting - H.Z. Yue; C. Yu; H.B. Li; C.B. Zhou; S.H. Chen; Z.S. Shao (Shock and Vibration)
Rock damage and vibration attenuation are the basis of blasting design, which will affect rock breaking results and the safety of structures (buildings). In this paper, the effect of blast-hole arrangement, delay time, and decoupling charge on the rock damage and the vibration attenuation in multihole blasting were numerically investigated. Through dynamic analysis software ANSYS/LS-DYNA, the JOHNSON_HOLMQUIST_CONCRETE (JHC) rock model and fluid-solid coupling method were used to establish single-hole and multihole rock blasting models. Based on the analysis of single-hole rock damage and vibration, firstly, the effect of the above three factors on the rock damage characteristics of multihole blasting was analyzed. Then, the extracted peak particle velocity (PPV) data of multihole blasting were fitted to the United States Bureau of Mines (USBM) equation to obtain the blasting vibration attenuation parameters (the site constant K and α). It is found that the blast-hole arrangement, delay time, and decoupling charge have a much smaller effect on α than K. At the same time, a delay-time-dependent model of PPV correction coefficient was proposed, and its rationality was verified by field data. The results obtained in this paper have reference significance for optimizing the blasting design and improving the blasting effect.